Turkish translations of self-help "Success" books :|a collage/bricolage of moral narratives and new life ethics - Akdoğan, Fazilet. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
This study analyzes the translation history of the success-based self-help literature in Turkish from the 1930s to the 1990s, focusing on the habitus and trajectories of the leading translators/authors whose agency paved the way in the transfer of this genre as well as depicting their specific translating/writing practices. It demonstrates that a cultural field of self-help has emerged mainly through translations since the 1930s in Turkey, and the success-based self-help books, which are considered as “moral narratives” in this study, have introduced a new ethical approach based on the metanarratives of capitalism and individualism. For the analysis of the translating/writing practices of the dominant translators/authors in the translation history under concern, a new conceptual tool, “collage/bricolage” is suggested and elaborated in this context as well. By examining the works of the dominant translators/authors through the concept of “collage/bricolage,” the study reveals the interrelatedness of translation and indigenous writing in the development of this genre in Turkish. It is illustrated that “collage/bricolage,” as the main form of translating/writing, has not only enabled these translators/authors to transfer some popular moral narratives into the Turkish culture but also served as a means of access to symbolic power and consecration in this field. The study also proves that collage as the paradigm of translation marks the continuation of the “telif” tradition in the twentieth century, in the sense theorized by Saliha Paker for the Ottoman translation history.
Keywords: Books -- Translation.; Success in literature.